2015
DOI: 10.5070/c421028860
|View full text |Cite
|
Sign up to set email alerts
|

The psorosis disease of citrus: a pale light at the end of the tunnel

Abstract: First reported in 1896, psorosis was the first citrus disease proven to be graft transmissible and also the first for which eradication and budwood certification programs were launched to prevent its economic damage. For many years psorosis etiology remained elusive, and only in 1986 was the disease associated with the presence of virus-like particles in infected plants. However, in the last 2 decades a virus with unusual morphology (Citrus psorosis virus, CPsV) was characterized and closely associated with ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Due to the similarity of BBS symptoms with those associated with psorosis, the disease was named Bahia-type psorosis (Nickel et al, 2007). But since CPsV is not its etiological agent, that denomination has been disregarded (Moreno et al, 2015). In 2006, Laranjeira et al suggested that BBS was transmitted by air-borne vectors with limited dispersion ability, strengthening the 6/15 hypothesis of a viral causal agent.…”
Section: Bahia Bark Scaling (Bbs)mentioning
confidence: 99%
“…Due to the similarity of BBS symptoms with those associated with psorosis, the disease was named Bahia-type psorosis (Nickel et al, 2007). But since CPsV is not its etiological agent, that denomination has been disregarded (Moreno et al, 2015). In 2006, Laranjeira et al suggested that BBS was transmitted by air-borne vectors with limited dispersion ability, strengthening the 6/15 hypothesis of a viral causal agent.…”
Section: Bahia Bark Scaling (Bbs)mentioning
confidence: 99%
“…In the case of Chile, citrus exports in 2020 were approximately 365 thousand tons, and constant growth is forecast for the coming years [4]. Citrus graft-transmissible disease (CGTD) is one of the main threats to this industry, causing estimated losses of 15% to 25% within infected orchards [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, some investigators isolated and identified CPsV (Nour-Eldin, 1956;Nour-Eldin, 1957;Fahmy et al, 2002). Citrus crop losses of graft-transmissible diseases were estimated as much as 15-25% (Moreno et al, 2015). These low losses may be due to the limited spread of the disease in Tucuman (Fawcett and Klotz, 1939).…”
Section: Introductionmentioning
confidence: 99%